Perforation of an Occult Carcinoma of the Prostate as a Rare Differential Diagnosis of Subcutaneous Emphysema of the Leg - Mirko Velickovic; Thomas Hockertz (Case Reports in Orthopedics)
We report a case of subcutaneous emphysema caused by perforation of the rectum due to a carcinoma of the prostate. Although rare, an abdominal cause must always be considered as a rare differential diagnosis of subcutaneous emphysema. As a matter of fact adequate diagnostic with rapid treatment is essential for the outcome.